2016
DOI: 10.1515/hsz-2016-0126
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 8 is an interactor of the metalloprotease meprin β within tetraspanin-enriched microdomains

Abstract: Meprin β is a dimeric type I transmembrane protein and acts as an ectodomain sheddase at the cell surface. It has been shown that meprin β cleaves the amyloid precursor protein (APP), thereby releasing neurotoxic amyloid β peptides and implicating a role of meprin β in Alzheimer's disease. In order to identify non-proteolytic regulators of meprin β, we performed a split ubiquitin yeast two-hybrid screen using a small intestinal cDNA library. In this screen we identified tetraspanin 8 (TSPAN8) as interaction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Recent studies demonstrated that ADAM10 localization and maturation is influenced by tetraspanins (TSPANs), building microdomains of protein clusters at the cell surface (Prox et al, 2012). In a yeast-two-hybrid approach TSPAN8 was identified as an interaction partner of meprin β, which was further proven by split-RFP and luciferase complementation assays (Schmidt et al, 2016). It was further demonstrated that APP together with meprin β is located in TSPAN8 enriched microdomains.…”
Section: Localizationmentioning
confidence: 99%
“…Recent studies demonstrated that ADAM10 localization and maturation is influenced by tetraspanins (TSPANs), building microdomains of protein clusters at the cell surface (Prox et al, 2012). In a yeast-two-hybrid approach TSPAN8 was identified as an interaction partner of meprin β, which was further proven by split-RFP and luciferase complementation assays (Schmidt et al, 2016). It was further demonstrated that APP together with meprin β is located in TSPAN8 enriched microdomains.…”
Section: Localizationmentioning
confidence: 99%
“…In regards to β-secretase cleavage, no direct interaction of tetraspanins with the β-secretase BACE1 has been reported. The metalloprotease Meprin β, which cleaves APP in a manner similar to BACE1 (Bien et al, 2012), interacts with Tspan8 and resides together with APP in TEMs (Schmidt et al, 2016). However, Tspan8 had no impact on the proteolytic activity of Meprin β towards APP.…”
Section: Tetraspanins As a Part Of A Multi-secretase Complexmentioning
confidence: 99%
“…Generation of destination vectors with RFP-A and RFP-B located 3′ of the Gateway recombination site has been previously described [ 42 ]. HEK293T cells were seeded at a density of 2.5 × 10 4 cells/mL in μ-dishes (Ibidi, Gräfelfing, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…HT29 cells were lysed in TNE (25 mM Tris, 150 mM NaCl, 5 mM EDTA, protease inhibitors) containing either 1% Triton X-100 or 1% Brij-98. Sucrose gradient preparation, centrifugation and analysis of the corresponding fractions were performed as described previously [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%